Reversible multivalent carrier redox exceeding intercalation capacity boundary - Yuanhe Sun; Rui Qi; Qi Lei; Wei Zhang; Haitao Li; Mengru Lin; Hao Shi; Jianrong Zeng; Wen Wen; Yi Gao; Xiaolong Li; Chunyi Zhi; et al. (Nature Communications)
Abstract Compared with widely established monovalent-ion batteries, aqueous multivalent-ion batteries promise higher capacity release by achieving multiple electron-transfer events per ion intercalation in the host material. Despite plausibility, this high-capacity dream is untenable with the total tolerable redox charge-transfer limit of the host material for all carrier species equally, which is historically assumed to depend on the material rather than the guest carrier itself, and the kinetic hysteresis induced by larger charge/radius ratios induced kinetic hysteresis further enlarges the divide. Herein, we report that copper carrier redox in vanadium sulfide (VS2) exceeds the intrinsic intercalation capacity boundary, with the highest capacity release as 675 mAh g-1 at 0.4 A g-1 among all VS2 cathodes previously reported. Operando X-ray absorption spectroscopy, operando synchrotron X-ray diffraction and composite ex situ characterization jointly demonstrated that intercalated divalent copper is preferentially involved in redox afforded extra electron transfer to form reversible monovalent copper pillars, thus not only ensuring stable topological de/intercalation with high capacity but also sustaining fast migration kinetic paths through reconfigurable pillar effects. Intercalated carrier redox reported here emphasizes the interlayer variable valence advantage of multivalent ions, providing insights into high-performance multivalent-ion storage chemistry in aqueous batteries.